Rancang Bangun Sistem Pendukung Keputusan Pemilihan Coffee Shop Terbaik Menggunakan Metode SAW (Studi Kasus: Pondok Pinang) - Eko Puji Saputro; Angga Septian M. N. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The coffee shop industry in the Pondok Pinang area is growing rapidly, providing many choices but also challenges for consumers in choosing a place that suits their preferences. This study aims to build a Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to objectively determine the best coffee shop. The research methodology includes observation, literature study, and web-based software design. The system evaluates alternatives based on five main criteria: price, menu variety, service, cleanliness, and facilities. The results show that the SAW method is effective in providing accurate recommendations, helping users make more efficient decisions in choosing the best cafe in Pondok Pinang.